Globalisierungsängste - gestern und heute [Concerns about globalisation - then and now] - Reinhard Spree (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
– In this paper the term `globalisation' means the international integration of nationally organised markets in conjunction with increasing cross-country flows of factors of production. According to this globalisation has been under way for centuries. Globalisation is not a completely autonomous, not even a solely market driven process. Historically, it is for the most part determined by decisions of nation states. In times of globalisation speeding up, typically social and political debates start about the driving forces, extent and impact of globalisation. Already two centuries ago, globalisation has been discussed in a similar way as today. Initially, there is a debate about the organisation of the foreign trade regime. Because change of social and economic structures is an integral part of globalisation, the debate about the impact of structural change is constituent in globalisation discourses. Winners and losers of the structural change try to improve their social position through foreign trade policy. These two levels of globalisation discourses are usually distorted by the argument that globalisation and the induced change of societal structures provoke adverse effects on the prevailing system of values. Because of this the globalisation discourse becomes a matter of emotion and disproportionately complex. The paper demonstrates the three levels of a typical globalisation discourse by using three examples. First, the actual globalisation discourse will be discussed. Second, in Germany at the beginning of the 20th century globalisation has been hotly debated under the heading “agrarian versus industrial state”. Third, the typical globalisation discourse can also be outlined by the dispute about the reform policy in Prussia in the early 19th century.
urn:nbn:de:bvb:19-epub-44-0
Keywords: B15; F13; N40; Z13; 330; globalisation; international trade; institutions; social norms; structural change